Ações empreendedoras no setor público: o desenvolvimento de uma escala - Ávila, Milena Abreu (2022)
Entrepreneurial action evidences the practices and results performed in the entrepreneur process, and can be manifested in different areas. In the public sector entrepreneurial action is still a subject little explored in the literature in developing countries, however, some Brazilian researchers have dedicated themselves to the theme. The studies by Nascimento and Andrade (2019) and Lacerda and Andrade (2021) proposed the development of theoretical models to identify how entrepreneurial action is appropriate in the public context. Lacerda and Andrade (2021) improved the theoretical model developed by Nascimento and Andrade (2019), identifying that public entrepreneurial action happen through the intertwining of some key categories: life orientation, individual or collective action, opportunity or tension situation, context organizational, external context, innovative practice, social interaction and social outcomes. The study proposes to verify the interrelationships between the categories of the theoretical model of entrepreneurial action in the public sector by Lacerda and Andrade (2021) through the development of a scale to be applied in municipal governments. We sought to understand and conceptualize the categories of entrepreneurial action in the public sector, validate the face and content of the proposed scale and describe the main aspects related to entrepreneurial action in municipal governments. This research is characterized as exploratory and presents a multi-method approach. In the qualitative approach, a bibliographic review was carried out, which is the main contribution to the elaboration of the instrument's assertions. Subsequently, the face and content of the instrument were validated through the operation of two pre-tests. The first with specialists in the area and the second with a small sample of the population. In the quantitative approach, a pilot test of the refined scale was carried out. The scale was applied to municipal civil servants working in city halls of the State of Minas Gerais who hold a public position, job or function. The data were tabulated and operationalized in statistical software: SPSS 22.0 and Smart PLS 3, using techniques of descriptive statistics analysis and structural equation modeling. It was identified that public entrepreneurial action in the municipal context occurs through the interrelation of the following categories: organizational context, opportunity, collective action, innovative practice and social results. In addition, it was possible to understand that opportunities to undertake in the public sector are compliant with the theory of creation, since public entrepreneurs act in situations of constant uncertainty and scarcity of resources. Thus, it was possible to identify the constructs that interrelate in a positive and significant way for the emergence of entrepreneurial action within the scope of municipal public management. The instrument developed can be used as a tool to assess the entrepreneurial capabilities and potential of the administrative structures of municipal governments.